2017
DOI: 10.1002/hed.24568
|View full text |Cite
|
Sign up to set email alerts
|

Central compartment management in patients with papillary thyroid cancer presenting with metastatic disease to the lateral neck: Anatomic pathways of lymphatic spread

Abstract: PTC rarely spreads to the lateral neck without depositing metastases within the central neck. This finding is supported by the anatomic pathways for lymphatic spread, not previously highlighted in the English literature. © 2017 Wiley Periodicals, Inc. Head Neck 39: 853-859, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 16 publications
(29 reference statements)
6
41
1
Order By: Relevance
“…Besides, our study further examined the pattern of lateral multiple-level metastases and found that among 72 PTMC patients with lateral multiple-level metastases, the two-, three-, and four-level simultaneous metastases were detected in 38, 25, and nine patients, respectively. Levels III + IV simultaneous metastases were the most frequently involved in the lateral two-level metastases, which was consistent with the anatomy of lymphatic drainage in the area of the thyroid ( 26 ). The three-level metastases including levels II, III, and IV were the most common patterns in N1b PTMC patients.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Besides, our study further examined the pattern of lateral multiple-level metastases and found that among 72 PTMC patients with lateral multiple-level metastases, the two-, three-, and four-level simultaneous metastases were detected in 38, 25, and nine patients, respectively. Levels III + IV simultaneous metastases were the most frequently involved in the lateral two-level metastases, which was consistent with the anatomy of lymphatic drainage in the area of the thyroid ( 26 ). The three-level metastases including levels II, III, and IV were the most common patterns in N1b PTMC patients.…”
Section: Discussionsupporting
confidence: 82%
“…Xiao et al ( 29 ) conducted ipsilateral LND for PTC patients and demonstrated that CPLN ≥ 2 was a reliable indicator of lateral LNM. Likhterov and colleagues ( 26 ) revealed that the incidence of lateral LNM significantly increased with the CPLN. Kim et al ( 24 ) have reviewed 658 N1b PTC patients and demonstrated that the bilateral central LNM (OR = 4.06, 95% CI: 2.29–7.18) and the unilateral central LNM (OR = 2.45, 95% CI: 1.53–3.92) were independent predictors for the lateral multilevel metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of lymphatic drainage follows the blood vessels that feed the gland. Ascending channels follow the superior thyroid artery and vein, draining the upper poles of the gland, while lymphatic drainage of the lower thyroid follows the inferior thyroid artery [20]. Since level VII lymph nodes were in anatomically continuous with level VI lymph nodes, it made sense that level VII LNM was associated with primary tumor location.…”
Section: Discussionmentioning
confidence: 99%
“…One drainage pathway is posterior to the carotid sheath and is responsible for level IV metastatic disease, whereas the other lymphatic pathways to the lateral neck can be found anterior to the carotid sheath. 13 The "Blood River" impedes the progress of lymph node metastasis. Because of the oblique BCT and right common carotid artery, RCSS became the "eyot" between the right carotid artery and the jugular vein and communicates with level VI and level IV through the areolar tissue, forming a "bridge" and "tunnel" across the "Carotid river" and under the "Jugular river," respectively.…”
Section: Discussionmentioning
confidence: 99%